2013
DOI: 10.3892/etm.2013.942
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Radix Pseudostellariae polysaccharides against exercise-induced oxidative stress in male rats

Abstract: The main purpose of this study was to examine the effect of Radix Pseudostellariae polysaccharides (RPPs) against swimming exercise-induced oxidative stress in male rats. A total of 40 male Wistar rats were randomized into four groups: the control (C), low-dose RPP supplementation (LRS), medium-dose RPP supplementation (MRS) and high-dose RPP supplementation (HRS) groups. The control group received saline solution and the supplementation groups received different doses of RPPs (100, 200 and 400 mg/kg body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Each of these antioxidant enzymes performs a reduction of a particular ROS. Several studies have reported a significant decrease in SOD, GPx, and CAT activity after exhaustive exercise [11,16,19]. The decrease in the activity of these enzymes may predispose tissues to free radical damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these antioxidant enzymes performs a reduction of a particular ROS. Several studies have reported a significant decrease in SOD, GPx, and CAT activity after exhaustive exercise [11,16,19]. The decrease in the activity of these enzymes may predispose tissues to free radical damage.…”
Section: Discussionmentioning
confidence: 99%
“…In the past three decades, several studies have indicated that oxidative stress can result in extensive lipid, protein, and DNA damage, which may lead to cell dysfunction, aging, carcinogenesis, and neurodegenerative and cardiovascular diseases [15]. Accumulated evidence has shown that increased antioxidant enzyme activity, increased resistance to oxidative stress, and lower levels of oxidative damage may protect against oxidative stressrelated damage to tissues and, on a microscopic level, to cellular macromolecules [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…GPx utilizes reduced glutathione (GSH) as a hydrogen donor for the removal of peroxides. CAT catalyzes the breakdown of hydrogen peroxide to form water, sharing this function with GPx [20]. Therefore, the improvement in the antioxidant enzymes activities can help to fight against fatigue.…”
Section: Effects Of Genistein On Serum Antioxidant Enzymes Of Micementioning
confidence: 99%
“…The protocol was adapted from a previous study with some modifications [10]. Briefly, the mice were dropped individually into an acrylic plastic pool (50 cm × 50 cm × 40 cm) filled with water to 30 cm deep and maintained at a temperature of 25 ± 0.5°C.…”
Section: Forced Swimming Testmentioning
confidence: 99%
“…Urea is formed in the liver as the end product of protein metabolism (Chen et al, 2013). During digestion, protein is broken down into small peptides and amino acids.…”
Section: Effects Of Pgp On Blood Urea Nitrogenmentioning
confidence: 99%